1998
DOI: 10.1152/ajprenal.1998.274.4.f635
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt modulates renal production of transforming growth factor-β in rats

Abstract: Transforming growth factors (TGF) are potent multifunctional polypeptides that are involved in renal function and glomerular sclerosis. We postulated that dietary salt modified renal production of TGF-β. An increase in dietary salt produced sustained increases in steady-state levels of mRNA for TGF-β1, -β2, and -β3 in the rat kidney. While serum concentration of TGF-β1 did not change, the 8.0% NaCl diet increased urinary excretion of TGF-β1, indicating enhanced renal production was the source of TGF-β1. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 45 publications
7
76
0
2
Order By: Relevance
“…32 These effects of high salt intake on target organs are linked to the fibrogenic activity of transforming growth factor (TGF)-b1, as TGF-b1 production has been demonstrated to increase during high salt intake. 33,34 Indeed, the overexpression of TGF-b1 mRNA was demonstrated in the left ventricle and kidneys after a high-salt diet in animal studies. 31 The present study demonstrated a positive correlation between albuminuria and serum CRP levels in treated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 These effects of high salt intake on target organs are linked to the fibrogenic activity of transforming growth factor (TGF)-b1, as TGF-b1 production has been demonstrated to increase during high salt intake. 33,34 Indeed, the overexpression of TGF-b1 mRNA was demonstrated in the left ventricle and kidneys after a high-salt diet in animal studies. 31 The present study demonstrated a positive correlation between albuminuria and serum CRP levels in treated hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the vascular smooth muscle hypertrophy and the ventricular hypertrophy in SHR-SP resulted directly from the severe hypertension, but that the renal damage may be associated not only with the hypertension but also with the local production of TGF-β. In addition, dietary salt has been reported to modulate production of TGF-β in the kidney (15,16). Ying and Sanders (15) reported that an increase in dietary salt produced sustained increases in expression of TGF-β1 mRNA in rat kidney, but no changes in serum concentration of TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤1 protein levels in urine and conditioned medium were determined by enzyme immunoassay (TGF-␤1 Emax ImmunoAssay System; Promega) as described previously (26). Mesangial cells were treated with 0.1 or 1.0 M polyamide or 1.0 M mismatch in the presence of 1.0 M PMA for 24 h. Conditioned medium was collected and diluted with TGF-␤1 sample buffer.…”
Section: Measurement Of Tgf-␤1 Proteinmentioning
confidence: 99%